Human after all: an exploration of Steven Galloway's The cellist of Sarajevo - Horvath, Steven (My University, 2010)
The MacEwan Book of the Year Student Contest invites students to submit creative and/or critical essay responses inspired by the university's current Book of the Year. Submissions are judged by MacEwan University's Book of the Year committee members. This work was the 2009/10 winning entry for Steven Galloway’s The Cellist of Sarajevo (2008) and was awarded Critical Essay winner.
Keywords: literary criticism; Cellist of Sarajevo; Steven Galloway; MacEwan Book of the Year